2019
DOI: 10.5194/acp-19-7609-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the formation of highly oxygenated organic molecules (HOMs) from alpha-pinene ozonolysis

Abstract: Abstract. Highly oxygenated organic molecules (HOMs) are important contributors to secondary organic aerosol (SOA) and new-particle formation (NPF) in the boreal atmosphere. This newly discovered class of molecules is efficiently formed from atmospheric oxidation of biogenic volatile organic compounds (VOCs), such as monoterpenes, through a process called autoxidation. This process, in which peroxy-radical intermediates isomerize to allow addition of molecular oxygen, is expected to be highly temperature-depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 47 publications
6
54
1
Order By: Relevance
“…The temperature dependence in PRAM is based on quantum chemical calculations wherein the autoxidation rates correspond to an activation energy of 24 kcal mol −1 . The activation energies vary for autoxidation of different RO 2 from α-pinene ozonolysis between 22 and 29 kcal mol −1 (Rissanen et al, 2015), leading to varying autoxidation rates at different temperatures (Roldin et al, 2019). It should be noted that the temperature dependence in PRAM is the first of its kind but needs further evaluation using recent measurements of HOM formation at different temperatures (e.g., Quéléver et al, 2019).…”
Section: Malte (Model To Predict New Aerosol Formation In Lowermentioning
confidence: 99%
“…The temperature dependence in PRAM is based on quantum chemical calculations wherein the autoxidation rates correspond to an activation energy of 24 kcal mol −1 . The activation energies vary for autoxidation of different RO 2 from α-pinene ozonolysis between 22 and 29 kcal mol −1 (Rissanen et al, 2015), leading to varying autoxidation rates at different temperatures (Roldin et al, 2019). It should be noted that the temperature dependence in PRAM is the first of its kind but needs further evaluation using recent measurements of HOM formation at different temperatures (e.g., Quéléver et al, 2019).…”
Section: Malte (Model To Predict New Aerosol Formation In Lowermentioning
confidence: 99%
“…Highly oxidized multifunctional molecules (HOMs), organic molecules with O : C ratios > 0.6, are the result of atmospheric autoxidation and have recently been subject to much investigation, in part because the extremely low volatilities arising from their high O : C ratios favour their condensation into the particulate phase. HOMs are most well characterized as the product of oxidation of the biogenic monoterpenoid compound α-pinene (Riccobono et al, 2014;Tröstl et al, 2016;Bianchi et al, 2017). Although globally biogenic volatile organic compound (BVOC) concentrations far exceed anthropogenic volatile organic compound (AVOC) concentrations, in the urban environment the anthropogenic fraction is far more significant.…”
Section: Introductionmentioning
confidence: 99%
“…Recent chamber studies have elucidated the contribution of individual species to particle nucleation, ammonia, and amines, greatly enhancing the rate of sulfuric acid nucleation (Kirkby et al, 2011;Almeida et al, 2013). In these studies, HOMs have been identified, formed through autoxidation mechanisms Riccobono et al, 2014;. These are key to early particle growth (Tröstl et al, 2016) and can nucleate even in the absence of sulfuric acid in chambers (Kirkby et al, 2016) and in the free troposphere (Rose et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Formation of highly oxygenated organic molecules (HOM) has been identified as a pathway for new particle formation and growth of SOA (Bianchi et al, 2019). Recent work has shown that alongside HOM formation from ozonolysis (Quéléver et al, 2019), 35 hydroxyl radical oxidation of monoterpenes is a large source of HOM (Berndt et al, 2016). Oligomerisation is another key pathway to formation of SOA and has been identified as important for monoterpenes including α-pinene and limonene (Hall and Johnston, 2011;Kourtchev et al, 2016;Kundu et al, 2012;Putman et al, 2011;Tolocka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%